2024
DOI: 10.1039/d3tc04217k
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature vapor reduction of graphene oxide electrodes for vertical organic field-effect transistors

Kun Qiao,
Qing Ma,
Junjia Wang
et al.

Abstract: Vertical organic field-effect transistors based on a low-temperature-prepared reduced graphene oxide electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Interestingly, there is no saturation current observed in the output characteristics, which is consistent with our previous findings in rGO-VOFETs and other graphene-VOFETs. 12,13,[23][24][25] In a subsequent study, we calculated the carrier mobility of organic semiconductors using the space-charge-limited current technique and found that the carrier mobility of the organic semiconductor is not the main limiting factor in this type of device. The highest potential current density is much larger than the value obtained for the device.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, there is no saturation current observed in the output characteristics, which is consistent with our previous findings in rGO-VOFETs and other graphene-VOFETs. 12,13,[23][24][25] In a subsequent study, we calculated the carrier mobility of organic semiconductors using the space-charge-limited current technique and found that the carrier mobility of the organic semiconductor is not the main limiting factor in this type of device. The highest potential current density is much larger than the value obtained for the device.…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of the GO film is ∼1 nm, indicating its monolayer structure. 24 Importantly, the high-coverage smooth surface was maintained after the reduction treatment (Fig. S1c, ESI†), which is essential to ensure its high conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation